Abuse and Neglect of the Elderly in India (Springer Singapore, 2018)
This book highlights different aspects of the problem of elder abuse and neglect in India, and discusses its forms as well as means of prevention, intervention and management. It presents a framework for understanding the occurrence of elder abuse and neglect in India, placing the discussion within the global context. Elder abuse and neglect is a growing concern in South Asia, and this is the first comprehensive account of the topic from India. It uses data from different parts of India to describe the various dimensions of elder abuse and neglect among different population categories and sections in society. Covering rural and urban areas in different states, it discusses current perspectives on elder abuse and neglect at the household level, widows, HIV-affected populations, and those residing in institutions. This book comprises views from experts in the field and is of interest to researchers and academics from the social and behavioural sciences, policy makers, and NGOs.